Hubungan Corporate Governance, Corporate Social Responsibilities dan Corporate Financial Performance Dalam Satu Continuum (Jurnal Akuntansi dan Keuangan, 2010)
This research aims to identify the influence of Good Corporate Governance, represented by institutional ownership and managerial ownership, on Corporate Social Responsibility and Corporate Financial Performance, and also to observe the possible influence of Corporate Social Responsibility on Corporate Financial Performance. This research examines 126 manufacturing companies which are listed in Indonesian Stock Exchange (ISX) and have issued an audited financial statement for 2006. The statistical method used to test the hypothesis is Path Analysis. The result suggests that Good Corporate Governance influences both the disclosure of Corporate Social Responsibility and Corporate Financial Performance and that Corporate Social Responsibility significantly influences Corporate Financial Performance. The result also suggests that CEO Tenure, the controlling variable, holds a significant influence on the disclosure of Corporate Social Responsibility. Yet, there is no strong evidence to support the type of industries as an influencing factor of Corporate Social Responsibility. Furthermore, we found that the latter condition would also apply when we analyze the influence of Corporate Secretary and Nomination and Remuneration Committee on Corporate Financial Performance. Abstract in Bahasa Indonesia: Penelitian ini bertujuan untuk mengidentifikasi pengaruh antara struktur Coorporate Governance yang diproksikan sebagai kepemilikan institusional, kepemilikan manajerial terhadap corporate social responsibility dan corporate social responsibility terhadap corporate financial performance. Penelitian menggunakan data sekunder dari laporan tahunan 2006 perusahaan publik yang terdapat di Pusat Referensi Pasar Modal (PRPM) Bursa Efek Indonesia (BEI). Sampel dalam penelitian ini sebanyak 126 perusahaan. Melalui pendekatan analisa jalur (path analysis) menunjukkan Good Corporate Governance yaitu kepemilikan managerial dan institusional mempunyai pengaruh terhadap kinerja perusahaan Good Corporate Governance yang diamati melalui kepemilikan managerial dan institusional, mempunyai pengaruh terhadap pengungkapan tanggung jawab sosial perusahaan (CSR). Pengujian variabel control, yaitu CEO Tenure mempunyai pengaruh terhadap pengungkapan tanggung jawab sosial perusahaan (CSR). Sedangkan jenis Industri tidak mempunyai pengaruh terhadap CSR. Untuk Corporate Secretary dan Komite Nominasi dan Remunerasi juga tidak mempunyai pengaruh terhadap kinerja perusahaan. Kata kunci: corporate governance, corporate social responsibility, corporate financial performance, kepemilikan institusional, kepemilkan mangerial, CEO tenure, corporate secretary, komite nominasi dan remunerasi